Literature Review: The Role of Saffron (Crocus sativus L) in Cosmetic Dermatology - Galih Sari Damayanti; Puguh Riyanto (Jurnal Kedokteran Diponegoro, 2023)
Background : Crocus sativus L known as saffron is widely discussed in Indonesia. Although saffron has been used since ancient times for medicinal and cosmetic purposes, scientific research on the mechanism of saffron in its role in promoting skin health is lacking. Objectives : This literature review is to determine the role of saffron in cosmetic dermatology. Methods : This article is a narrative research. The library sources that used was carried out through the database Google Scholar, PubMed, and Cochrane. The article search does not limit study design or study level. All articles were searched from 2012 to June 2023. The study inclusion criteria included: data available in English and Indonesian. Exclusion criteria were articles on the benefits of using saffron in the other field of dermatology and the use of saffron in combination with other topical active ingredients. Results : There were 16 articles which meet the criterias. It was found that saffron play role in the cosmetic dermatology such as in skin aging, melasma, as a photoprotection agents, skin moisturizer, prevention and treatment of skin cancer, as well as preparation of cosmetic products. Saffron has antioxidant, antiinflammatory, antipigmentation, antiwrinkle, anticarcinogenic and photoprotective activities. Conclusion : Crocus sativus L is a natural ingredient that has the potential to be further developed into medicinal forms, both oral and topical preparations because it is proven to have various pharmacological effects that play role in the cosmetic dermatology.